Characterization of lignin stabilized waste magnesia refractory bricks for potential applications as construction aggregates - Boyoung Yoon; Jaewoo Jung; Woojin Lee; Changho Lee (Case Studies in Construction Materials)
The rapid depletion of natural aggregate resources has led to the exploration of recycled aggregates as sustainable alternatives. The steel industry annually generates 28 million tons of magnesia–based waste refractories (WMRs), making their incorporation into construction materials a potential strategy for resource conservation. However, WMR recycling poses a challenge because of its susceptibility to volume expansion during hydration. This study evaluated the feasibility of an environmentally friendly additive, lignosulfonate (LS), for stabilizing crushed waste magnesia refractory bricks (CWMR) to explore the potential application of WMR as construction aggregates. The swelling properties, including the free swell index (FSI) and the swell pressure (Ps), and mechanical properties including unconfined/uniaxial compressive strength (qU), shear wave velocity (VS), and thermal conductivity (λ) of LS stabilized CWMR (CWMLS) were evaluated over different curing periods at varying LS contents (LSc). Hydration transformed CWMR from sand-like to highly plastic silt-like, resulting in a significant FSI of 250 % and Ps of 5.2 MPa. LS effectively stabilized CWMR, as indicated by decreased FSI and Ps, and enhanced qU and VS. Microscopic observation and mineralogy analyzes confirmed that LS stabilizes CWMR by adsorbing onto its surface. Stabilization of thermal conductivity at higher LSc over curing periods further supports these interactions. Macroscopic behavioral analyzes give stabilized effect of 94.3 % at LSc = 5 % with minimal improvement at higher LSc. These findings highlight LS as a promising stabilizer for mitigating hydration-induced expansion and improving the mechanical properties of CWMR, supporting its application as a recycled aggregate in construction.